The influence of the problem based learning model assisted by LKPD Liveworksheet on student learning motivation - Pertiwi (Al-Khazini, 2023)
The transformation of 21st century education requires teachers as facilitators of students’ learning in schools to be able use the lates learning aids with easier access. Problem based learning model assisted by liveworksheet can be used as an option to train students’ 21st century skills as well as train their digital literacy skill which can alse increase their learning motivation. This research was carried out at SMP Negeri 2 Barombong in August – September 2022 with material on works, energy and simple machines. The population in this research were all students in class VIII SMP Negeri 2 Barombong totally 342 students occupy classes A-J so that by using the simple random sampling technique class VIII B was assigned as the experimental class and VIII C as the control class. The research instrument used a learning motivation questionnaire whose result were processed using descriptive analysis techniques and inferential analysis with independent samples t-test. The result of this research showed that the problem based learning model assisted by liveworsheet can be increase students’ learning motivation.